Combining ability of maize inbred lines containing genes from Zea diploperennis for resistance to Striga hermonthica (Del.) Benth - Yallou, C.G.; Menkir, A.; Adetimirin, Victor O.; Kling, J.G. (Wiley, 2009)
Maize (Zea mays) is a staple food crop in sub-Saharan Africa, but itsproduction is threatened byStriga hermonthica(Del.) Benth. Transferof resistance genes from wild relatives may increase resistance toS. hermonthicain tropical maize. The objective of this study was todetermine the combining ability of resistance toS. hermonthicaamonglines containingZea diploperennisand tropical germplasm. Forty-fivediallel crosses of 10 inbred lines were evaluated in an alpha-latticedesign with and without artificialStrigainfestation at two locationseach in the Republic of Benin and Nigeria for 3 years. Results ofanalyses showed that only general combining ability (GCA) meansquare was significant (P¼0.01) for number of emergedStrigaplants(NESPP), while both GCA and specific combining ability (SCA) meansquares were significant for host damage score (HDS) and grain yieldunderStrigainfestation. The ratio of GCA to SCA mean squares forthe three traits varied from 3.5 to 57.5. Although GCA·environmentinteraction was significant for the three traits, two inbred linescontainingZ. diploperennis(ZD 551) and tropical (TZL TC 87)germplasm had negative and significant GCA effects for NESPP andHDS and positive GCA effects for grain yield underStrigainfestationin the two countries. Correlation between NESPP and HDS was strongand significant (r= 0.87, P¼0.01). Our results highlight the impor-tance of harnessing useful genes from wild relatives to improveresistance toS. hermonthicain adapted maize germplasm.